2007
DOI: 10.1073/pnas.0706566104
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of protein and hydration-water dynamics in biological membranes

Abstract: The dynamical coupling between proteins and their hydration water is important for the understanding of macromolecular function in a cellular context. In the case of membrane proteins, the environment is heterogeneous, composed of lipids and hydration water, and the dynamical coupling might be more complex than in the case of the extensively studied soluble proteins. Here, we examine the dynamical coupling between a biological membrane, the purple membrane (PM), and its hydration water by a combination of elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
175
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(188 citation statements)
references
References 56 publications
(71 reference statements)
13
175
0
Order By: Relevance
“…Energy resolved incoherent neutron scattering, especially in the elastic (EINS) and quasielastic (QENS) scattering modes, have been informing us on water dynamics under different conditions for decades. Because the method relies on incoherent scattering, samples need not be crystalline or even monodisperse and measurements can be performed on highly complex systems such as living cells 2 or stacks of natural membranes 3 . The incoherent neutron scattering cross section of hydrogen is more than an order of magnitude larger than that of other atomic nuclei usually found in biological material and their isotopes, including deuterium, and the development of in vivo specific deuterium labelling methods permitted the focus on water dynamics in complex biological samples, and its coupling with biological function and activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy resolved incoherent neutron scattering, especially in the elastic (EINS) and quasielastic (QENS) scattering modes, have been informing us on water dynamics under different conditions for decades. Because the method relies on incoherent scattering, samples need not be crystalline or even monodisperse and measurements can be performed on highly complex systems such as living cells 2 or stacks of natural membranes 3 . The incoherent neutron scattering cross section of hydrogen is more than an order of magnitude larger than that of other atomic nuclei usually found in biological material and their isotopes, including deuterium, and the development of in vivo specific deuterium labelling methods permitted the focus on water dynamics in complex biological samples, and its coupling with biological function and activity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, however, the onset of hydration water translational diffusion at 200 K, in a membrane, was not observed to trigger a dynamical transition in the membrane protein 25,26 , suggesting a more complex interaction between protein, water, and the membrane lipid environment. Recent neutron scattering studies, using specific deuterium labelling, confirmed that a dynamical transition coincides with the onset of hydration water translational diffusion, in the case of a soluble proteins 27 , but not in the case of a membrane protein 3,28 .…”
Section: Introductionmentioning
confidence: 99%
“…solvent molecules must flow past or around protein molecules. Below 200 K, solvent flow and translational diffusion are negligible (Weik et al, 2004;Wood et al, 2007Wood et al, , 2008 and so contraction should become nearly isotropic.…”
Section: Origins Of Disorder On Coolingmentioning
confidence: 99%
“…[10][11][12][13][14][15] Interestingly, such studies indicate coupling between the dynamics of water and biological objects which may imply a strong interaction between the solute and the hydration shell. 16,17 It is well known that structure, dynamics and even macroscopic properties of water are determined by the strong intermolecular interactions between the hydrogen-bonded water molecules. 18 However, the question which still remains unanswered is whether water molecules at interfaces, such as in the hydration layer of the membrane, display a behavior similar to the bulk water.…”
Section: Introductionmentioning
confidence: 99%